Distribution of darkling beetles (Tenebrionidae) in Malaysia - H., Darya; Adam, Nur Azura; Lau, Wei Hong; R. H., Izfa; Maa, Ali; Ahmed, Agha M. (AkiNik Publications, 2016)
The Indo-Malayan region has Stenochiinae, Alleculinae, Amarygmini and Ulomini as the largest number of higher groups belonging to Tenebrionidae family. Since last few years, the forests of Southeast Asia especially Malaysia have changed dramatically as a result of logging and development that caused some changes in the wildlife more particularly insects. The distribution of insect species is widely existed in Malaysia and causing economic damage to the number of plants and agricultural crops. Therefore, this study was conducted on the distribution status of three subfamilies (Stinochiinae, Tenebrioninae and Diaperinae) of family Tenebrionidae especially considering darkling beetles in Malaysia as it has significant impact worldwide. All the insects were collected through different methods to observe their distribution and seasonal abundance. These traps were monitored monthly and a total number of Tenebrionids were calculated from all study sites. A total number of 120 beetles were collected represented 30 species and 17 genera. However, the most abundant genera were Tribolium and Promethis and some species rarely found in the area. The collected information regarding distribution of Tenebrionid will be helpful in future to manage their population below economic damage.